Meteorology, soil temperature and moisture of Jarvis Creek watershed, Interior Alaska, 2011-2016 - Anna Liljedahl (Arctic Data Center, 2017)
The overall project assessed the linkages and controls of a subarctic glacier-permafrost hydrological system from a watershed-scale perspective using field measurements, remote sensing and numerical modeling. Jarvis Creek (634km²), which feeds the Delta and Tanana River in Interior Alaska, was studied as a proxy of the observed mountain glacier melting and permafrost degradation that has been documented across the Arctic region in recent decades. The specific objectives were to 1) assess the hydrologic fluxes (including streamflow source components), stores, pathways and the role of glacier wastage on watershed hydrology, through hydrologic and geochemical field measurements as well as numerical and statistical modeling; 2) quantify the effect of glaciers and permafrost on recent historical (1960-present) hydrologic fluxes and storage by combining remote sensing, field measurements of glacier mass balance, and hydrology with a heat- and mass transfer model, and 3) project the future hydrologic regime using custom-derived downscaled climate projections. The purpose of this dataset was to quantify the spatial and temporal variability in meteorology and soils from the lowland (572 m.a.s.l.) to the mountains (1746 m.a.s.l.) across a 6 year time period. Hourly measurements include air temperature, relative humidity, wind speed, incoming solar radiation, rainfall and snow depth. Measurement depths of soil temperature and moisture were at <1.5 and <0.5 m depth, respectively. The meteorology, soil temperature and moisture dataset informed assessments of watershed hydrology.